(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This article examines the emergence of glass objects in the Bronze and Iron Ages in ancient Turan, their manufacturing technologies, development in terms of shape and color, and their religious-symbolic significance. Glass beads, necklaces, rings, and other ornaments provide important information about the aesthetic views, religious beliefs, and social stratification of ancient society. The study analyzes the findings of glass and glass-paste objects, their symbolic meanings (water, sun, life, eternity, fertility, etc.), and the technical skills of artisans, including polishing, drilling, coloring, and working with alloys. The results contribute to a deeper understanding of the cultural heritage, craftsmanship traditions, and religious worldviews of the peoples of ancient Turan.